Isolation and characterization of lambda pleu bacteriophages. - Davis, M G (1977)
In the Escherichia coli lysogen HfrH73 described by Shimada et al. (1973), none of the enzymes coded for by the leucine operon is synthesized due to an insertion of phage lambda into cistron leuA. The orientation of lambda in the chromosome is ara leuDCB lambda JAN leuA. After heat induction of the lysogen, plaque-forming transducing phages of two types are formed at low frequency. One type (e.g., lambda pleu9) transduces leuD, leuC, and leuB strains to prototrophy. The other type (e.g., lambda pleu 13) transduces leuA strains to prototrophy. lambda pleu 13 forms lysogens at low frequency (about 0.2%) by integration into the leucine operon. These lysogens are unstable, segregating phage-sensitive clones at high frequency (about 1%). Phages carrying different portions of the leucine operon were formed by aberrant excision after heat induction of strain CV437 (leuA371 lambda pleu13). A phage carrying the entire leucine operon (lambda K2) was constructed by a cross between lambda pleu9 and lambda pleu13. An analysis of leucine-forming enzyme levels in strains lysogenized with lambdaK2 indicated that leuO and leuP are present and functional in lambda K2. leu-specific messenger ribonucleic acid from E. coli hybridizes to the heavy (r) strand of lambdaK2. The leucine operon of lambda G4 pleuABCD (an S7 derivative of lambda K2) exists intact on a 7.3 x 10(6)-dalton fragment (lambdaG4EcoRI-B) generated by cleavage with endonuclease EcoRI. Heteroduplexes formed between lambda G4 and lambda show a 5.4 x 10(6)-dalton piece of bacterial deoxyribonucleic acid (DNA) replacing a 4.5 x 10(6)-dalton piece of lambda DNA starting at 0.46 fractional unit on the map of lambda. Fragment lambda G4EcoRI-B has about 0.6 x 10(6) daltons of lambda DNA from the b2 region at one end and about 1.4 x 10(6) daltons of lambda DNA from the int region at the other end.